The development of physical characteristics in adolescent team sport athletes: A systematic review - Tingelstad, L. M.; Raastad, T.; Till, K.; Luteberget, L. S. (PLOS ONE, 2023)
Background Physical development during adolescence is crucial for athletes in team sports, as it prepares them for the high sport demands at the senior level. While physical development in non-athletes are well-documented, a comprehensive understanding of adolescent athletes` development, including the potential effects of team sports participation and training load, is lacking.